Molar heat capacity and electrolytic conductivity of aqueous solutions of [Bmim][MeSO 4] and [Bmim][triflate] - Lin, Pei-Yin; Soriano, Allan N.; Caparanga, Alvin R.; Li, Meng-Hui (Thermochimica acta, 2009)
Here we report the new measurements of molar heat capacity, C P and electrolytic conductivity, σ for aqueous solutions of 1-butyl-3-methylimidazolium methylsulfate, [Bmim][MeSO 4] and 1-butyl-3-methylimidazolium trifluoromethanesulfonate, [Bmim][triflate]. Heat capacities were measured from 303.2 to 353.2 K with a differential scanning calorimeter. Electrolytic conductivities were measured from 293.2 to 353.2 K with a commercial conductivity meter. The estimated uncertainties of C P and σ measurements were ±2 and ±1%, respectively. The present measurements of C P and σ were presented as a function of temperature and composition. An excess molar heat capacity C P E expression using the Redlich–Kister equation for the temperature and composition dependence was used to represent the measured C P and a modified empirical equation was used to correlate the temperature and composition dependence of the measured σ of the studied systems. The applied correlations represent the C P and σ measurements satisfactorily. The C P and σ values presented in this work are, in general, of sufficient accuracy for most engineering-design calculations.